Possibilities of prevention of recurrent pterigium after surgical treatment - A.N. Bochkareva; V.V. Egorov; G.P. Smolyakova; E.L. Sorokin; P.A. Banshchikov (РМЖ "Клиническая офтальмология")
Bochkareva A.N.1, Egorov V.V.1,2, Smolyakova G.P.1,2, Sorokin E.L.1,3, Banshchikov P.A.1 1 The Khabarovsk branch of “Eye Microsurgery” Federal State Institution named after S.N. Fyodorov 2 Postgraduate Institute for Health Care Professionals, Khabarovsk, Russia  3 Far-Eastern State Medical University, Khabarovsk, Russia  Aim: to evaluate the clinical effectiveness of the method developed by us to prevent the recurrence of pterygium II and III after its resection. Patients and Methods: we have developed our own technique for creating a biological barrier in pterygium surgery. The method includes the use of amnioplasty outside the limbus zone after resection of the pterygium to prevent its recurrence. The analysis of the clinical efficacy of the developed technique was carried out. Clinical material — 46 eyes with primary pterygium II and III. The main group consisted of 22 eyes, in which the amnioplasty was performed according to the method developed by us. The comparison group consisted of 24 eyes, in which the scleral defect in the limbus zone was covered by a flap of the amniotic membrane. The method of surgical resection of the pterygium head was the same in both study groups. The criterion for comparison of the groups was the existence and frequency of pterygium recurrences in 10-12 months after the surgery. Results: in the comparison group, the graft was characterized by a sluggish vitalization, while in the main group an adequate vitilization was observed. After 1 month of observation there was an excessive limbus vascularization and tension of the lacrimal caruncle in 5 eyes of the comparison group. Despite the intensification of anti-inflammatory treatment, there was a relapse of the pterygium in 3 eyes, which required a repeated surgery using the technology applied in the main group. Conclusion: essential advantages of the developed method of surgical treatment of the pterygium are elimination of its basis — the vascularized Tenon’s capsule of the medial angle of eye; localization of the biological barrier in the area of the semilunar fold; grafting of the sclera defect by preserved conjunctival tissue. This approach allowed to achieve a statistically significant increase in transplant vitalization in the main group, against the comparison group. Assessment of the clinical efficacy of the developed technology has shown that there were no relapses during the observation period of up to 12 months, although in the comparison group relapses occurred in 3 eyes (12.5%). Key words: pterygium, recurrent pterygium, amnioplasty outside the limbus zone, conjunctival flap, amniotic membrane, corneal epithelization, graft vitalization, tear osmolarity. For citation: Bochkareva A.N., Egorov V.V., Smolyakova G.P. et al. Possibilities of prevention of recurrent pterigium after surgical treatment // RMJ “Clinical ophthalmology”. 2018;1:20–25.